Disseminated CMV infection and HLH in a patient with well-controlled HIV and ulcerative colitis. Issue 2 (11th February 2019) - Cockbain, Beatrice Clare; Mora Peris, Borja; Abbara, Aula; So, Chun Wah; Cooke, Graham
Abstract : We present a case of haemophagocytic lymphohistiocytosis (HLH) in the context of disseminated cytomegalovirus (CMV) viraemia in a 50-year-old man with well-controlled HIV infection and ulcerative colitis (UC), for which he was receiving azathioprine. Peak CMV viral load was 371 000 copies/ml with evidence of end-organ CMV in the lungs and colon. A bone marrow biopsy showed evidence of haemophagocytosis of platelets, neutrophils and erythrocytes. The azathioprine was stopped, and he received intravenous ganciclovir and corticosteroids with suppression of the CMV viral load and resolution of the HLH.